BIBLIOMETRIC ANALYSIS OF SAFETY MANAGEMENT: A COMPREHENSIVE REVIEW - Yudha, Dwi (JURNAL BISNIS STRATEGI, 2023)
This article provides a comprehensive review of safety management research conducted between 1982 and 2023 using bibliometric analysis. The analysis of 969 articles published during this period shows that safety management research has steadily grown over the years, with the majority of research conducted in the United States and Europe. The most commonly mentioned term is "safety management," and the highest number of articles were published in 2022, followed by 2020 and 2019. The study also identifies the most prolific authors and journals in the field. China is identified as a leading player in the field of Safety Management research and publications, with the highest frequency of mentions. The USA has the highest TC, indicating the highest number of citations for research and publications in the field of Safety Management. The findings of this study provide valuable insights into the current state of safety management research, which can be used to identify research gaps and prioritize areas for future research. The article also provides a comprehensive reference list of the most influential articles and authors in the field, serving as a starting point for researchers who are new to this area of study.